Genomic Survey of Salt Acclimation-Related Genes in the Halophilic Cyanobacterium Euhalothece sp. Z-M001 - Yang, Hee Wook; Song, Ji Young; Cho, Sung Mi; Kwon, Hak Cheol; Pan, Cheol-Ho; Park, Youn-Il (NATURE PUBLISHING GROUP, 2020)
Like other halophilic cyanobacterial genomes, the de novo-assembled genome of Euhalothece sp. Z-M001 lacks genes encoding keto-carotenoid biosynthesis enzymes, despite the presence of genes encoding carotenoid-binding proteins (CBPs). Consistent with this, HPLC analysis of carotenoids identified beta-carotene and zeaxanthin as the dominant carotenoids. CBPs coexpressed with the zeaxanthin biosynthesis gene increased the survival rates of Escherichia coli strains by preventing antibiotic-induced accumulation of reactive oxygen species (ROS). RNA-seq analysis of Euhalothece revealed that among various salt resistance-related genes, those encoding the Na+ transporting multiple resistance and pH adaptation (Mrp) systems, glycine betaine biosynthesis enzymes, exopolysaccharide metabolic enzymes, and CBPs were highly upregulated, suggesting their importance in hypersaline habitats. During the early phase of salt deprivation, the amounts of beta-carotene and zeaxanthin showed a negative correlation with ROS content. Overall, we propose that in some halophilic cyanobacteria, beta-carotene and zeaxanthin, rather than keto-carotenoids, serve as the major chromophores for CBPs, which in turn act as effective antioxidants.
Keywords: ORANGE CAROTENOID PROTEIN; SYNECHOCYSTIS SP PCC-6803; BETA-CAROTENE; FUNCTIONAL-ANALYSIS; TERMINAL DOMAIN; EPS PRODUCTION; BIOSYNTHESIS; HALOTOLERANT; HYDROXYLASE; MECHANISM